ROUTLEDGE HISTORY OF CRIME IN AMERICA ([S.l.])
1 online resource
Keywords: Covering a broad chronology from the colonial era to the present, this volumes 28 chapters reflect the diverse approaches, interests and findings of an international group of new and established scholars working on American crime histories today. The book is organized around major themes in crime history, including violence, science and technology, culture, gender and organized crime, and it addresses pressing contemporary concerns such as mass incarceration and the racial politics of crime in modern America.It also engages with the history of crime literature, film and popular culture from colonial execution sermons to true crime television in the twenty-first century. The volume is alert to continuities and diversity over time and place in the history of American crime, notably in chapters on the South, the West and the impact of urbanization on practices and ideas about crime and law enforcement in different periods of the American past. The Routledge History of Crime in America is an indispensable, interdisciplinary resource for students and researchers working in areas of crime, crime policy, punishment, policing and incarceration.